2020
DOI: 10.4103/jfmpc.jfmpc_505_20
|View full text |Cite
|
Sign up to set email alerts
|

Cefdinir associated bloody stool in Riyadh infant: A case report

Abstract: Cefdinir is one of the broad spectrum cephalosporin used as a replacement to amoxicillin in allergic pediatric population. There are reports of forming red stool in patients receiving cefdinir along with iron or iron containing preparations. This is a benign interaction and wane upon completion/discontinuation of cefdinir therapy. This case report describes a 6-month-old boy whose parents were distressed when they found reddening of their ward's diaper while taking cefdinir in presence of iron supplements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…Several reports have shown that the Cefdinir-iron complex produces reddish stool. [3][4][5] Most of these cases involve a similar scenario of prescribing Cefdinir while the infant is taking either a multivitamin with iron or iron-fortified formula. However, this case highlighted other iron-containing formulations, and multivitamins, Unexpectedly, healthcare providers and pharmacists are still unaware of these possible innocuous side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that the Cefdinir-iron complex produces reddish stool. [3][4][5] Most of these cases involve a similar scenario of prescribing Cefdinir while the infant is taking either a multivitamin with iron or iron-fortified formula. However, this case highlighted other iron-containing formulations, and multivitamins, Unexpectedly, healthcare providers and pharmacists are still unaware of these possible innocuous side effects.…”
Section: Discussionmentioning
confidence: 99%